Elastic Scattering of 28Si from Target Nuclei 27Al at Energies 70, 80, 90 and 100 Mev by Strong Absorption Model (SAM) (Global Journal of Science Frontier Research, 2012)
The differential cross-section for the elastic scattering of heavy ion 28Si from target nuclei 27Al at different projectile energies has been studied in terms of the Strong Absorption Model of Frahn and Venter[1] using the three parameters version of this model. In this paper we find that a reasonably good description to the angular distribution of the experimental elastic scattering data is possible.
Keywords: Elastic scattering; SAM; strong absorption model